Negotiating Conflict at the Intersection: Identity and Problem Solving - Toni Alexander; Lesli K Pace; Melissa Odegard (Academic Chairpersons Conference Proceedings, 2023)
An interactive workshop focused on improving self-awareness and understanding of conflict management strategies to improve effectiveness in conflict resolution as a chairperson.
Keywords: Conflict Management; Self-Awareness; Intersectional Identity; Higher Education Leadership; Servant Leader